2021
DOI: 10.1080/02791072.2021.1971343
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Beliefs about the Therapeutic Use of Psychedelic Drugs among Psychologists in the United States

Abstract: Psychologists are a vital component of mental health treatment and their perceptions of psychedelic-assisted therapy are critical for future implementation. This cross-sectional quasiexperimental electronic survey study explored the attitudes about psychedelics used in treatment among 366 clinical psychologists in the United States. Participants expressed cautiously favorable attitudes toward therapeutic psychedelic experiences but indicated concern about possible psychiatric and neurocognitive risks. Most par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
31
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 37 publications
9
31
1
1
Order By: Relevance
“…(2018) suggested that part of the reason for negative attitudes toward classic hallucinogens was the fact that psychiatrists were more likely to treat individuals who experienced severe adverse effects, which include development of psychosis or hallucinogen‐persistent perceptual disorder. It is also unclear whether the inclusion of MDMA in the current study and in Davis et al.’s (2021) research affected this perception of harm.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…(2018) suggested that part of the reason for negative attitudes toward classic hallucinogens was the fact that psychiatrists were more likely to treat individuals who experienced severe adverse effects, which include development of psychosis or hallucinogen‐persistent perceptual disorder. It is also unclear whether the inclusion of MDMA in the current study and in Davis et al.’s (2021) research affected this perception of harm.…”
Section: Discussionmentioning
confidence: 58%
“…(2018) and Davis et al. (2021) (see Table S1), counselors held similar views regarding the risk for long‐term cognitive impairment yet were more unsure about the risk for psychiatric disorders. Nearly two thirds of psychiatrists and nearly half of psychologists endorsed the view that psychedelics may increase one's risk for psychiatric disorders, compared to only one third of counselors.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The use of psychedelics, such as psilocybin (magic mushrooms), Lysergic acid diethylamide (LSD), and ayahuasca have drawn attention due to their noticeable ability to alter consciousness in personally meaningful, therapeutic, and spiritual ways [ 10 ]. Indeed, clinical trials on psilocybin demonstrated its efficacy in reducing cancer-related anxiety and depression, treatment-resistant depression, major depressive disorder (MDD), and substance misuse [ 11 ]. This review aims to highlight and discuss the potential of fungal biologics including psilocybin, LSD and others as therapeutic alternatives (mycotherapy) for alleviating the symptoms of mental health disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Corrigan et al surveyed patients’ opinions on psilocybin therapy 31 . A study by Davis et al assessed American psychologists’ opinions on psychedelics 32 , while Hearn et al surveyed counselors in the United States 33 . All studies have so far used unvalidated self-developed questionnaires and presented their results as a cross-sectional overview of responses for each item.…”
Section: Introductionmentioning
confidence: 99%